Air-conditioning system with underfloor air distribution integrated solar chimney in data center. (2017) - Gao, Yang; Liu, Jinxiang; Yuan, Xiaolei; Zhang, Kai; Yang, Yujia; Wang, Yu
Abstract: Data centers have the characteristics of high heat production from equipment and uneven temperature distribution. Thus, in order to improve the thermal environment in data centers, this paper puts forward an air-conditioning system with under-floor integrated solar chimney. The improved system can also reduce energy consumption due to annual cooling. A typical data center model is built and verified with experiments. Based on this model, the new model integrated solar chimney is built and simulated. The results show that after integrating the solar chimney, the heat island effect impairs and the temperature of all compared points have a decline, which reached an average decline of about 4.4 ℃. In addition, integrated solar chimney system improves the mixing of cold air and hot air effectively.